Business Administration Training For SME Women in Menur Pumpungan Village - Widhi Ariestianti Rochdianingrum; Siti Rokmi Fuadati; Ulfah Setia Iswarah; Teguh Gunawan (OJS Universitas Muhammadiyah Gresik, 2020)
Community service activities are carried out to provide administrative training to women who are MSMEs and menur pumpungan villages. Administration training provided in the form of training and assistance in the preparation of simple bookkeeping and business ethics in running a business. Training activities and assistance in preparing simple books is important so that mothers can know with certainty how much business revenues and business expenses are run. In addition to the existence of simple bookkeeping can be known the number of items that sell. Business ethics training is conducted to provide provisions for SMEs to be confident in marketing goods that are sold according to existing conditions so that consumer confidence can be achieved. The results of this activity can be concluded that UMKM mothers have understood the importance of bookkeeping and can begin to compile simple bookkeeping in their business by continuing to be accompanied by a team. In business ethics training, mothers have understood the importance of giving consumers rights. This is shown by mothers who want to redesign packaging labels that include more information for consumers such as expiration date, composition of materials used and the date of production of the product.